2021
DOI: 10.5606/tftrd.2021.7983
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, etiology, and biopsychosocial risk factors of cervicogenic dizziness in patients with neck pain: A multi-center, cross-sectional study

Abstract: Objectives: This study aims to investigate the prevalence, etiology, and risk factors of cervicogenic dizziness in patients with neck pain. Patients and methods: Between June 2016 and April 2018, a total of 2,361 patients (526 males, 1,835 females; mean age: 45.0±13.3 years; range, 18 to 75 years) who presented with the complaint of neck pain lasting for at least one month were included in this prospective, cross-sectional study. Data including concomitant dizziness, severity, and quality of life (QoL) impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Dizziness is one of the most common reasons for consultation in adult patients [ 1 , 2 ]. It is an umbrella term used to describe various sensations, including vertigo, disequilibrium, lightheadedness, or presyncope ( Table 1 ) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dizziness is one of the most common reasons for consultation in adult patients [ 1 , 2 ]. It is an umbrella term used to describe various sensations, including vertigo, disequilibrium, lightheadedness, or presyncope ( Table 1 ) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical observation of a large number of cases (1000 cases) found that cervicogenic dizziness accounted for 89% of all dizziness, or vertigo [ 5 ]. Cervical spondylosis was one of the common causes of dizziness in the elderly in a community survey [ 1 ]. Among patients with cervical vertebral whiplash injuries, the prevalence of dizziness has been variously reported, ranging from 20% to 90% [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the type of symptoms and other signs, such as restrictions on the range of movement (ROM), the most common classifications in clinical care are cervicogenic dizziness (CGD), tension-type headache (TTH) and mechanical chronic neck pain (MCNP) [ 5 , 13 , 14 ]. These clinical symptoms are more frequent in women than in men [ 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these variables may be predicted in patients with CP based on pain intensity. For this reason, it is suggested that psychological distress and kinesiophobia may be pain mediators in patients with CP [ 16 , 22 , 23 , 24 , 25 ]. Recent evidence suggests a relationship between pain intensity, cervical ROM, psychological distress and kinesiophobia [ 16 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%